Multiscale structural control of linked metal–organic polyhedra gel by aging-induced linkage-reorganization. Issue 38 (26th August 2021) - Wang, Zaoming; Villa Santos, Christian; Legrand, Alexandre; Haase, Frederik; Hara, Yosuke; Kanamori, Kazuyoshi; Aoyama, Takuma; Urayama, Kenji; Doherty, Cara M.; Smales, Glen J.; Pauw, Brian R.; Colón, Yamil J.; et al.
Abstract : By a controlled post-synthetic aging process, we demonstrate a protocol to induce the linkage reorganization in metal–organic polyhedra-linked gel networks, leading to the control of gel structures over multiple length scales and their properties. Abstract : Assembly of permanently porous metal–organic polyhedra/cages (MOPs) with bifunctional linkers leads to soft supramolecular networks featuring both porosity and processability. However, the amorphous nature of such soft materials complicates their characterization and thus limits rational structural control. Here we demonstrate that aging is an effective strategy to control the hierarchical network of supramolecular gels, which are assembled from organic ligands as linkers and MOPs as junctions. Normally, the initial gel formation by rapid gelation leads to a kinetically trapped structure with low controllability. Through a controlled post-synthetic aging process, we show that it is possible to tune the network of the linked MOP gel over multiple length scales. This process allows control on the molecular-scale rearrangement of interlinking MOPs, mesoscale fusion of colloidal particles and macroscale densification of the whole colloidal network. In this work we elucidate the relationships between the gel properties, such as porosity and rheology, and their hierarchical structures, which suggest that porosity measurement of the dried gels can be used as a powerful tool to characterize the microscale structural transition of their corresponding gels. This aging strategy can be applied in other supramolecular polymer systems particularly containing kinetically controlled structures and shows an opportunity to engineer the structure and the permanent porosity of amorphous materials for further applications.